Association Between Hemoglobin Levels, Duration of Hemodialysis, and Mental Health Outcomes in CKD Patients: A Cross-Sectional Study - Mardiyah, Adiyati; Julianti, Erna; Zulkifli, Zulkifli; Giovana, Lyah; Raharjo, Dian Tri (Journal of Applied Nursing and Health, 2026)
Background: Chronic kidney disease (CKD) is a global health problem that can progress to end-stage renal failure requiring hemodialysis. Patients on long-term hemodialysis often experience anemia and mental health problems, yet evidence from Indonesia and other LMICs on the relationship between clinical factors and mental health remains limited. This study aims to analyze the association between hemodialysis duration and hemoglobin levels with mental health and emotional role functioning in hemodialysis patients. Methods: This quantitative study used a cross-sectional design. A consecutive sampling method was used, involving 75 patients undergoing hemodialysis from hospitals across Bangka Island between June and August 2024. Inclusion criteria are undergoing hemodialysis twice a week, and exclusion criteria are experiencing sudden shortness of breath and being in unstable or emergency conditions during data collection. Independent variables are years on hemodialysis and hemoglobin; dependent variables are the Mental Health and Role Emotional domains of the SF-36. The SF-36 questionnaire is a valid instrument used in patients undergoing hemodialysis to study physical activity and rehabilitation. Data analysis included univariate analysis to determine the mean and standard deviation, as well as bivariate analysis using the Pearson correlation test using SPSS Version 26. Results: The mean score for the Mental Health (MH) domain was 59.22, and for the Role Emotional (RE) domain, it was 30.67, indicating that patients undergoing hemodialysis had relatively low scores in both domains. A significant correlation was found between years on hemodialysis and hemoglobin levels with mental health and role emotional scores  (P =0,0001) (P value < 0,05). Conclusion: Mental health and role emotional issues in patients with CKD undergoing hemodialysis are still understudied, which negatively affects their quality of life. Healthcare professionals need to conduct comprehensive assessments that consider not only the physical but also the mental health and emotional role aspects of these patients. Many patients undergoing hemodialysis have poor mental health and emotional functioning. Factors such as years on hemodialysis and hemoglobin levels are associated with improvements in these domains.